Peptide-Protein Binding Investigated by Far-IR Spectroscopy and Molecular Dynamics Simulations - Cote, Yoann (Biophys J, 2017)
Molecular dynamics (MD) simulations and far-infrared (far-IR) spectroscopy were combined to study peptide binding by the second PDZ domain (PDZ1) of MAGI1, which has been identified as an important target for the Human Papilloma Virus. PDZ1 recognizes and binds to the C-terminal end of the E6 protein from high-risk Human Papilloma Virus. The far-IR spectra of two forms of the protein, an unbound APO form and a HOLO form (where the PDZ1 is bound to an 11-residue peptide derived from the C terminus of HPV16 E6), were obtained. MD simulations were used to determine the most representative structure of each form and these were used to compute their respective IR spectra by normal mode analysis. Far-UV circular dichroism spectroscopy was used to confirm the secondary structure content and the stability through temperature-dependent studies. Both the experimental and calculated far-IR spectra showed a red shift of the low-frequency peaks upon peptide binding. The calculations show that this is coincident with an increased number of hydrogen bonds formed as the peptide augments the protein β-sheet. We further identified the contribution of surface-bound water molecules to bands in the far-IR and, through the calculations, identified potential pathways for allosteric communication. Together, these results demonstrate the utility of combining far-IR experiments and MD studies to study peptide binding by proteins.